Comparison of HBV-DNA Levels with Biochemical and Microbiological Parameters for Chronic Hepatitis Evaluation, Bursa, Turkey - Sanem Karadag Gecgel (Pasteur Institute of Iran, 2021)
Introduction: HBV-DNA levels are used to diagnose chronic hepatitis B (CHB) disease, determine the infection phase, decide on the treatment, and determine the disease course. We aimed to compare the microbiological and biochemical parameters of patients followed up with chronic hepatitis B pre-diagnosis in our hospital according to their HBV-DNA levels. Methods: HBV-DNA levels were analyzed with the Real-Time PCR method in blood samples of 500 pre-diagnosed CHB patients between February-June 2018, retrospectively. The biochemical parameters of the patients were measured by an automatic biochemical immunoassay analyzer (Beckman Coulter DXI 800, USA), and the microbiological parameters of patients were determined by an automatic analyzer (Roche Cobas 6000, Germany). The differences between the values of biochemical and microbiological parameters of patients were determined according to HBV-DNA. Results: Mean corpuscular volume (MCV) was higher in patients with hepatitis B virus-DNA (HBV-DNA)>20000 IU/mL than patients with negative HBV-DNA, HBV-DNA<2000 IU/mL, and HBV-DNA 2000-20000 IU/mL (P<0.05, P<0.01, P<0.01). Gamma-glutamyl transpeptidase (GGT) was lower in patients with HBV-DNA ranging from 2000-20000 IU/mL than HBV-DNA negative patients, HBV-DNA<2000 IU/mL and HBV-DNA>20000 IU/mL (P<0.05). Albumin was lower in patients with  HBV-DNA>20000 IU/mL than patients with HBV-DNA 2000-20000 IU/mL and HBV-DNA<2000 IU/mL (P<0.01). Hepatitis B surface antigen (HBsAg) levels were higher in patients with HBV-DNA 2000-20000 IU/mL than HBV-DNA negative patients, and patients with HBV-DNA<2000 IU/mL and HBV-DNA>20000 IU/mL (P<0.05, P<0.05, P<0.05). Albumin was individually correlated with the HBV-DNA by 2.9%, negatively (P<0.01). Conclusion: MCV, GGT, albumin, HBsAg levels might be used as indicators to diagnose CHB disease, establish the infection phase, decide the treatment, and determine the course of the disease together with HBV-DNA levels.